Biochemical Markers, Medications, and COVID-19 Complications in Vaccinated Versus Unvaccinated Pakistani Patients - Durrani, Hameed Mumtaz; Uzair, Muhammad Talha; Mukhtar , Abdullah; Sadaf, Hina; Nasir, Rabea; Raza, Syed Irfan (Journal of Rawalpindi Medical College, 2025)
Objective This study aimed to explore the association between COVID-19 vaccination and prolonged post-COVID symptoms (long COVID) in adults reporting this condition. Material and Methods This is a cross-sectional design of the study design. With the consent, the data were collected through questionnaire questionnaires from patients (N=308) who visited OPD or were admitted to the hospital with COVID-19 infection. The patient demographic details, vaccination status, type of complications, and haematological and pathological blood tests including complete blood count (CBC), D-dimer, white blood cells (WBC), and platelet count along with medication details the patient used. Patients used either Group I medicines (Panadol and Azomax) or Group 2 (Azomax, Surbex-Z, Loprine, Multivitamin, Ivermectin, and anti-allergy). Using. The data was analyzed using characteristics and inferential statistics such as chi-square and Fischer’s exact tests. Results A significant association is observed between the duration of infections and the type of medication used (group 1 & group 2). For infection duration of more than a week with group 1 medications 65.9% (p<0.001) and for two weeks or more with group II medications 87.9% (p<0.001). Data analysis showed no correlation between vaccination status and POST-Covid-19 complications. A significant association was observed when WBC count was compared with neuro-psychological and cardiovascular complications at the 0.05 significance level (p-values <0.001 & 0.008). No significant association was observed between neutrophil count and the type of vaccination used. Conclusion: Biochemical and haematological diagnostic markers, such as blood CBC, platelet count, and neutrophil count, exhibit a correlation with the type of medication used in managing COVID-19 complications, highlighting differences between vaccinated and unvaccinated patients. Keywords: Blood CBC, Neutrophil count, Platelet count, COVID-19, Hypertension